(untitled) - The World Bank (WB) (Washington DC., 2011)
This course aims to ensure that course participants have a functional and integrated understanding of urban land dynamics, and to demonstrate through a case library of good practices around the world how to effectively utilize policies and planning instruments to manage urban growth and achieve sustainable, equitable, and efficient development outcomes. The target audience includes urban practitioners, policymakers, and city managers involved in land use planning in developing countries who are confronted with the various challenges accompanying rapid urbanization.
Keywords: Land use,Soil science,Sử dụng đất,Khoa học đất; Planning,Kế hoạch